Hydrophobically Modified siRNAs Silence Huntingtin mRNA in Primary Neurons and Mouse Brain - Julia F Alterman; Lauren M Hall; Andrew H Coles; Matthew R Hassler; Marie-Cecile Didiot; Kathryn Chase; Jasmin Abraham; Emily Sottosanti; Emily Johnson; Ellen Sapp; Maire F Osborn; Marian Difiglia; et al. (Elsevier, 2015)
Applications of RNA interference for neuroscience research have been limited by a lack of simple and efficient methods to deliver oligonucleotides to primary neurons in culture and to the brain. Here, we show that primary neurons rapidly internalize hydrophobically modified siRNAs (hsiRNAs) added directly to the culture medium without lipid formulation. We identify functional hsiRNAs targeting the mRNA of huntingtin, the mutation of which is responsible for Huntington's disease, and show that direct uptake in neurons induces potent and specific silencing in vitro. Moreover, a single injection of unformulated hsiRNA into mouse brain silences Htt mRNA with minimal neuronal toxicity. Thus, hsiRNAs embody a class of therapeutic oligonucleotides that enable simple and straightforward functional studies of genes involved in neuronal biology and neurodegenerative disorders in a native biological context.